“Pet effect” patterns: Dynamics of animal presence and caregiver affect across (tele)work and non-work contexts - Joni Delanoeije; Miriam Engels; Mayke Janssens (PLoS ONE, 2025)
Human-animal interactions (HAI) may relate to animal caregivers’ affect, also referred to as the “pet effect”. However, studies have not explored these associations in work contexts or evaluated longitudinal patterns of HAI with other activities across work and non-work contexts, and their associations with caregiver emotions. We therefore assess momentary associations between HAI during (tele)work and non-work time and positive and negative caregiver affect (PA/NA), identify person-level patterns of longitudinal HAI state trajectories, and analyze cross-level moderating effects of these patterns on momentary associations between HAI and PA/NA. First, we evaluated associations between momentary HAI and caregiver PA/NA including the moderating role of momentary work state (teleworking vs. not working). Second, using a data-driven approach, we applied sequence analysis to determine heterogeneity in state trajectories amongst caregivers using working activity and animal presence in five possible states (working at work/teleworking with animal/teleworking without animal/not working with animal/not working without animal), which we labelled as animal-work constellations. Similar trajectories of animal-work constellations across caregivers were grouped into clusters with recognizable patterns. Third, we assessed whether such patterns moderated momentary associations between HAI and caregiver PA/NA. Caregivers (Npersons =  324) completed ecological momentary survey data during five days with 10 prompts per day (Nobservations =  16,127) between 2017 and 2024. Results showed that momentary associations between HAI and affect were moderated by momentary work state and person-level animal-work constellation pattern, contextualizing the “pet effect”. Our results highlight the importance of microlevel investigations of animal-work constellations and validates the novel use of sequence analysis to explore the role of context and time.